A Historical Overview of Research on Babesia orientalis, a Protozoan Parasite Infecting Water Buffalo - He, Lan; Liu, Qin; Yao, Baoan; Zhou, Yanqin; Hu, Min; Fang, Rui; Zhao, Junlong (Frontiers in Microbiology, 2017)
Babesiosis is a globally important zoonotic disease caused by tick-borne intraerythrocytic protozoan of the genus Babesia (phylum apicomplexa). In China, there are five species that infect cattle buffalo and cause great economic loss, which include Babesia bigemina, Babesia bovis, Babesia major, Babesia ovata and Babesia orientalis . Among them, B. orientalis is the most recently identified new Babesia species epidemic in China. This review summarized the work done in the past 33 years to give an overview of what learned about this parasite. This parasitic protozoan was found in 1984 in Central and South China and then named as B. orientalis in 1997 based on its differences in transmitting host, morphology, pathogenicity and characteristics of in vitro cultivation when compared with B. bigemina and B. bovis. It was found that Rhipicephalus haemaphysaloides is the transmitting vector and water buffalo is the only reported host. Phylogenetic analysis based on the 18S rRNA gene also confirmed that B. orientalis is a new species. After species verification, four diagnostic methods including semi-nest PCR, loop-mediated isothermal amplification assay (LAMP), reverse line blot hybridization assay (RLB) and real-time PCR were established for lab and field use purposes. Genomic sequencing was conducted and the complete genomes of mitochondria and apicoplast were annotated. Future work will be focused on developing effective vaccines, identifying drug targets and screening useful drugs for controlling B. orientalis in water buffalo.